Human endogenous retroviruses and ADHD. (August 2014) - Balestrieri, Emanuela; Pitzianti, Mariabernarda; Matteucci, Claudia; D'Agati, Elisa; Sorrentino, Roberta; Baratta, Antonia; Caterina, Rosa; Zenobi, Rossella; Curatolo, Paolo; Garaci, Enrico; Sinibaldi-Vallebona, Paola; Pasini, Augusto
Abstract Objectives. Several lines of evidences suggest that human endogenous retroviruses (HERVs) are implicated in the development of many complex diseases with a multifactorial aetiology and a strong heritability, such as neurological and psychiatric diseases. Attention deficit hyperactivity Disorder (ADHD) is a neurodevelopmental disorder that results from a complex interaction of environmental, biological and genetic factors. Our aim was to analyse the expression levels of three HERV families (HERV-H, K and W) in patients with ADHD. Methods. The expression of retroviral mRNAs from the three HERV families was evaluated in peripheral blood mononuclear cells (PBMCs) from 30 patients with ADHD and 30 healthy controls by quantitative RT-PCR. Results. The expression levels of HERV-H are significantly higher in patients with ADHD compared to healthy controls, while there are no differences in the expression levels of HERV-K and W. Conclusions. Since the ADHD aetiology is due to a complex interaction of environmental, biological and genetic factors, HERVs may represent one link among these factors and clinical phenotype of ADHD. A future confirmation of HERV-H overexpression in a larger number of ADHD patients will make possible to identify it as a new parameter for this clinical condition, also contributing to deepen the study on the role of HERVs in the neurodevelopment diseases.